Desain Bahan Ajar Kinematika Gerak Berbasis Konflik Kognitif Mengintegrasikan Program Tracker - Larasati Gustia Ayopma; Fatni Mufit (Universitas PGRI Semarang, 2023)
Physics subjects often cause difficulties for students in understanding abstract concepts so that misconception often occur, including misconceptions about motion kinematics. Solution of problems is to develop teaching material that can improve conceptual understanding and remediate misconceptions about motion. This study aims to determine the validity of cognitive conflict-based physics teaching materials using the tracker program on motion kinematics so as to improve conceptual understanding and remediate misconceptions in high school students. This type of research is development research by following the Plomp development procedure. This research is limited to two stages, namely preliminary research and prototyping phase until the validity of product. The results of preliminary research indicate that there is misconception in the concept of motion kinematics. The teaching material is designed according to the cognitive conflict model syntax and in the third syntax there is an experiment using the Tracker program. The results of the validity test by 3 physics lecturers obtained an average validation of 0.807. The results off this study state that the teaching materials are in very valid criteria in terms of content, presentation, language, and appearance.Keywords: Cognitive Conflict, Tracker Program, Misconception.